Medicinal Chemistry Meets Electrochemistry: Redox Potential in the Role of Endpoint or Molecular Descriptor in QSAR/QSPR - Nesměrák, Karel (Mini reviews in medicinal chemistry, 2020)
Many biochemical reactions are based on redox reactions, therefore the redox potential of a chemical compound may be related to its therapeutic or physiological effects. Study of redox properties of com-pounds is a domain of electrochemistry. The subject of this review is the relationship between electro-chemistry and medicinal chemistry, with a focus on quantifying these relationships. A summary of the relevant achievements in the correlation between redox potential and structure, therapeutic activity, resp., is presented. The first part of the review examines the applicability of QSPR for prediction of redox properties of medically important compounds. The second part brings exhaustive review of publications using redox potential as a molecular descriptor in QSAR of biological activity. Despite the complexity of medicinal chemistry and biological reactions, it is possible to employ redox potential in QSAR/QSPR. In many cases, this electrochemical parameter plays essential but rarely absolute role.